1997
DOI: 10.1063/1.474233
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative adsorption of network forming fluids onto crystalline surfaces: Structure and connectivity of the interface

Abstract: Effects of weak surface fields on the density profiles and adsorption of a confined fluid near bulk criticality A comparison of density functional and integral equation theories vs Monte Carlo simulations for hard sphere associating fluids near a hard wall Density profiles and first layer adsorption isotherms of a network forming fluid near a crystalline surface are investigated using the Percus-Yevick approximation for the associative Henderson-Abraham-Barker ͑HAB͒ equation. The fluid molecule is represented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…This means that the adsorbate has an additional (energetic and entropic) impact from its bulk, which induces a correlation for the adsorbed species. The correlation through the bulk is particularly pronounced when the pair interaction in the fluid is attractive enough to induce the clustering [6,7]. Then, the intra-cluster correlation, arising due to the cluster connectivity, enhances the adsorption in comparison with the monomeric case.…”
Section: Introductionmentioning
confidence: 97%
“…This means that the adsorbate has an additional (energetic and entropic) impact from its bulk, which induces a correlation for the adsorbed species. The correlation through the bulk is particularly pronounced when the pair interaction in the fluid is attractive enough to induce the clustering [6,7]. Then, the intra-cluster correlation, arising due to the cluster connectivity, enhances the adsorption in comparison with the monomeric case.…”
Section: Introductionmentioning
confidence: 97%
“…The effects of directional attractive forces leading to the formation of networks (specific for hydrogen bonded liquids, such as water) are neglected for the moment. If necessary these phenomena can be taken into account using the methods developed in 9 . In the simplest excluded volume approximation the bulk equation of state is…”
Section: Theorymentioning
confidence: 99%
“…To this end, the associative analogue of the Henderson-Abraham-Barker approach [54] was formulated [55] and it was applied to describe dymerizing fluids [55][56][57], polymers [58,59], the network forming fluids [60] close to a hard and adhesive surfaces and ionic fluids close to a charged wall [61]. The developed approach was also applied to describe the adsorption of polymers [58,62,63] and network forming fluids [64] onto crystalline surfaces. It was shown that the intramolecular correlations in polymer chains lead to the cooperative increase in the surface coverage which takes place under the conditions of a strongly diluted case.…”
Section: Some Applications and Conclusionmentioning
confidence: 99%